1985
DOI: 10.2136/sssaj1985.03615995004900050029x
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Transformation of Applied Phosphorus In Calcareous Lebanese Soils

Abstract: Though the initial reactions of P in soils are important with respect to plant growth and efficient fertilizer use, the reactions that occur with time have received less research attention, and may have even more important implications for these aspects. In order to monitor changes in applied P after fertilization, six calcareous soils were incubated up to 200 d with P solutions and periodically extracted with NaHCO3, and inorganically fractioned. Soil batches were equilibrated with P solutions ranging from 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Indeed, in Mediterranean soils, Fe oxides seem to be involved in long-term P sorption. Ryan et al (1985b) found, for six Lebanese soils, that the decrease in P extractability with time was related to Fed. Torrent (1987) found that the slow sorption for a group of 20 clays of Mediterranean soils could be described by a modified Elovich equation (C = Co -qt), the slope of which, q, was correlated with Fed.…”
Section: Slow (Long-term) Sorptionmentioning
confidence: 93%
“…Indeed, in Mediterranean soils, Fe oxides seem to be involved in long-term P sorption. Ryan et al (1985b) found, for six Lebanese soils, that the decrease in P extractability with time was related to Fed. Torrent (1987) found that the slow sorption for a group of 20 clays of Mediterranean soils could be described by a modified Elovich equation (C = Co -qt), the slope of which, q, was correlated with Fed.…”
Section: Slow (Long-term) Sorptionmentioning
confidence: 93%
“…Basal nutrients and plant growth conditions were as described by Genc et al (2007). Calcium carbonate powder (0.5%, w/w) was added in the sand to simulate calcareous sandy soil and to reduce P availability (Ryan et al, 1985;Westermann, 1992). Three P rates (7.5, 22.5, and 75 mg P kg 21 sand as KH 2 PO 4 ) were used in the experiments for severely P-deficient, moderately P-deficient, and P-adequate plants, respectively.…”
Section: Plant Growth and P Analysismentioning
confidence: 99%
“…Smaller particles form tighter bonds with P because they have more surface area (Carreira et al 2006). Amorphous minerals tend to sorb P more rapidly than crystalline material for similar reasons (Ryan et al 1985). Distinctions concerning the type and intensity of P bonding are important because these issues address the mobility and plant availability of P in dryland soil.…”
Section: Introductionmentioning
confidence: 99%